Текстова стратегія палімпсеста в поезії Василя Стуса - Поліщук, Я. (Слово і Час, 2018)
Автор розглядає табірну поезію В. Стуса (1938 – 1985), одного з найвидатніших українських
інтелектуалів другої половини ХХ ст., у контексті зміни культурних епох і текстових стратегій.
У формулі палімпсестів поет-дисидент шукав естетичної універсальності. Вона передбачає
імпліцитне заперечення цензури й можливість текстових варіацій. Але ця формула також
націлена на подолання закостенілої кондиції мови, ідеологічно заангажованої та колоніально
впослідженої. Палімпсест – це тяжіння до поезії неконвенційної, невербалізованої, абсолютної.
У цьому сенсі поезія Василя Стуса, міцно пов'язана з літературною традицією, стає латентним
виявом постмодерної культури. The author interprets Vasyl Stus’ (1938–1985) prison poetry in the context of changes of cultural
epochs and text strategies. Using the formula of palimpsests the poet-dissident tries to find aesthetic
universality. This form of the text implies the denial of censorship and the possibility of the poem’s
variations (1). Besides this, the formula also aims to overcome the outdated language condition (2)
which is ideologically engaged and marked by the consequences of colonialism. Palimpsest is the
gravitation to the unconventional nonverbalized and absolute poetry (3). In this way the poems by
Vasyl Stus are closely connected with classical tradition and at the same time they become a latent
manifestation of the postmodern culture.
Vasyl Stus is the artist, who worked on the borderlines of cultural epochs. His writings were absolutely
different from official literature of socialistic realism, which had a certain matrix of language at that time.
The first poetry books of V. Stus show that the author was out of any frames. The writers of western
classical literature were the landmarks in his own creative work, at the time when such literature was
perceived as a threat in USSR. An ideal reader, about whom Stus could dream, was absent, because
that culture had already lost him at the crossroads of times and aesthetic strategies. Vasyl Stus
essentially departs from the fixed text, which could be understood as immortalized and imperishable
but also as stiff and dead. The poet was in search for ways of updating classical tradition in literature.
Metaphor and irony – as two most inherent means of his artistic language – confirm these searches.
Perception of Stus’ poetry resembles the shape of sinusoid. The author was unknown during his life.
Only few people who were close to him could read his works. After the poet’s death, particularly in
1990, the Ukrainian reader found some barriers in perception of his poems. Firstly he regarded Stus’
poetry as evidence, an act of struggle. Secondly, the reader was faced with rationalism and complexity
of the images of the ‘palimpsest’, which were opposite to Ukrainian lyrics, adapted in mass culture. A
certain prejudice that exists to this day is the result of such perception. Palimpsest is the main means
of Stus’ poetry. It is difficult for understanding and needs a special culture of perception. Such writings
should be identified as a cultural challenge, as an appeal to overcome stereotypes and barriers in
the reception of modern poetry. Автор рассматривает лагерную поэзию В. Стуса (1938–1985),
выдающегося украинского интеллектуала второй половины ХХ ст.,
в контексте смены культурных эпох и текстовых стратегий. В формуле палимпсестов поэт-диссидент стремился обрести
эстетическую универсальность. Она предусматривает имплицитное отрицание цензуры и возможность текстовых вариаций. Но также
эта формула нацелена на преодоление закостеневшей кондиции языка, идеологически ангажированной и колониально униженной.
Палимпсест – это тяготение к поэзии неконвенциональной, невербализированной, абсолютной. В этом смысле поэзия В. Стуса,
тесно связанная с литературной традицией, становится латентным проявлением постмодерной культуры.